2018
DOI: 10.9755/ejfa.2018.v30.i3.1639
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of phenolic compounds extraction with antioxidant activity from açaí, blueberry and goji berry using response surface methodology

Abstract: The aim of this study was to determine the best extraction conditions of phenolic compounds present in açaí, blueberry and goji berry fruits using the response surface methodology (RSM). The phenolic compounds profile by high-performance liquid chromatography, antioxidant activity was also determined. A factorial 23 design was used to analyze the effect of the solvent (ethanol and water), time (30 and 60 min) and temperature (30 °C and 60 °C) on the extraction of total phenolic compounds (TPC) and activity ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…According to Yamaguchi et al (2015), among the phenolic compounds present in açaí, anthocyanins stand out as the main class, cyanidine-3-glucoside and cyanidine-3-rutinoside being the predominant forms, representing 30% of TPC, and being responsible for the purple color of the fruit. The monomeric anthocyanin content found in FDAP was lower (Table 1) than that reported by Moura et al (2018), who optimized anthocyanin extraction conditions from açaí pulp (410.24 mg/100 g (d.b.)) and blueberries (874.17 mg/100 g (d.b.)).…”
Section: Bioactive Compounds and Antioxidant Activitymentioning
confidence: 59%
See 2 more Smart Citations
“…According to Yamaguchi et al (2015), among the phenolic compounds present in açaí, anthocyanins stand out as the main class, cyanidine-3-glucoside and cyanidine-3-rutinoside being the predominant forms, representing 30% of TPC, and being responsible for the purple color of the fruit. The monomeric anthocyanin content found in FDAP was lower (Table 1) than that reported by Moura et al (2018), who optimized anthocyanin extraction conditions from açaí pulp (410.24 mg/100 g (d.b.)) and blueberries (874.17 mg/100 g (d.b.)).…”
Section: Bioactive Compounds and Antioxidant Activitymentioning
confidence: 59%
“…in Colombian pasteurized frozen açaí pulp. According to Moura et al (2018), the main phenolic compounds found in açaí were myricetin, epicatechin, catequin, and rutin, which are directly related to the antioxidant capacity of the fruit. According to Yamaguchi et al (2015), among the phenolic compounds present in açaí, anthocyanins stand out as the main class, cyanidine-3-glucoside and cyanidine-3-rutinoside being the predominant forms, representing 30% of TPC, and being responsible for the purple color of the fruit.…”
Section: Bioactive Compounds and Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The goji berry fruit, which is also rich in minerals, contains 11 essential minerals and 21 trace minerals. [1][2][3][4][5] The taurine extracted from the goji berry fruit is involved in many physiological and biochemical events; such as cell membrane stabilization, antioxidation, detoxification, osmoregulation, neuromodulation, especially brain and retinal development. It is known that one of its most important features is its antioxidant effect, so it often plays a role in daily life and health practices.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, medium optimization is required since it encourages the enhancement of biobutanol production, which can result in a lower production cost, resulting in a more cost-effective ABE fermentation, particularly when scaling up a butanol synthesis process. To further prove the efficacy of medium optimization, several successful applications have been proven for optimization for bioethanol production, pre-optimization alkaline protease production, and even for phenolic compounds extraction (Al-Shorgani et al, 2016;Sharma et al, 2017;de Moura et al, 2018). Generally, there are many types of strategies employed for medium optimization to improve the efficiency of the production medium such as central composite design (CCD), Box Behnken design, Plakett-burman design, Taguchi design, and even Response Surface Methodology (RSM) in which each design has its functional properties and advantages (Singh et al, 2017).…”
mentioning
confidence: 99%